Preferencias Psicoterapéuticas: Versión argentina de las escalas PEX-1 y C-NIP-v1.1 - Santangelo, Pablo Rafael; Conde, Karina (Pontificia Universidad Católica del Perú, 2022)
We sought to adapt to the Argentine context two scales that assess psychotherapeutic preferences: The Cooper-Norcross Preferences Inventory (C-NIP-v1.1) and the Questionnaire of Preferences and Experiences of Psychotherapy for the Patient (PEX-1). We administered both scales in a sample of N=600 people (non-probabilistic). We performed internal consistency, dimensional, and item level analyzes. The internal consistency coefficients were adequate for the total scale and, in general, for each dimension. The confirmatory factor analysis evidenced an adequate fit to the original structures. The performance of the items for the scale and its dimensions was acceptable with few exceptions. The psychometric properties of the C-NIP-v1.1 and the PEX-1 are suitable for their application in our context.

Se buscó adaptar al contexto argentino dos escalas que evalúan preferencias psicoterapéuticas: el Inventario de Preferencias de Cooper-Norcross (C-NIP-v1.1) y el Cuestionario de Preferencias y Experiencias de Psicoterapia para el Paciente (PEX-1). Ambas escalas fueron administradas a N=600 personas (muestra no probabilística). Se realizaron análisis de consistencia interna, dimensionales, y sobre los ítems. Los coeficientes de consistencia interna fueron adecuados para las escalas y sus dimensiones. Los análisis factoriales confirmatorios demostraron un ajuste aceptable a sus estructuras originales. El desempeño de los ítems fue óptimo, con algunas excepciones. Las características psicométricas del PEX-1 y C-NIP-v1.1 indicarían que se ajustan a la aplicación en nuestro contexto.

Nous avons cherché à adapter deux échelles qui évaluent les préférences psychothérapeutiques au contexte argentin: le Cooper-Norcross Preferences Inventory (C-NIP-v1.1) et le Patient Psychotherapy Preferences and Experiences Questionnaire (PEX-1). Les deux échelles ont été administrées à N = 600 personnes (échantillon non probabiliste). Des analyses de cohérence interne, dimensionnelle et sur les éléments ont été réalisées. Les coefficients de cohérence interne étaient adéquats pour les échelles et leurs dimensions. Les analyses factorielles de confirmation ont démontré un ajustement acceptable à leurs structures d'origine. La performance des articles était optimale, à quelques exceptions près. Les caractéristiques psychométriques du PEX-1 et du C-NIP-v1.1 indiqueraient qu'ils correspondent à l'application dans notre contexte.

Procuramos adaptar duas escalas que avaliam as preferências psicoterapêuticas ao contexto argentino: o Inventário de Preferências Cooper-Norcross (C-NIP-v1.1) e o Questionário de Preferências e Experiências de Psicoterapia do Paciente (PEX-1). Ambas as escalas foram aplicadas a N = 600 pessoas (amostra não probabilística). Foram realizadas análises de consistência interna, dimensional e sobre os itens. Os coeficientes de consistência interna foram adequados para as escalas e suas dimensões. As análises fatoriais confirmatórias demonstraram um ajuste aceitável às suas estruturas originais. O desempenho dos itens foi ótimo, com algumas exceções. As características psicométricas do PEX-1 e C-NIP-v1.1 indicariam que eles se encaixam na aplicação em nosso contexto.
Psychotherapeutic Preferences: The Argentine Version of the PEX-1 and C-NIP-v1.1 Scales
Préférences psychothérapeutiques: version argentine des échelles PEX-1 et C-NIP-v1.1
Keywords: Psychotherapeutic preferences; Psychotherapy; Psychometry; Argentina; Preferencias psicoterapéuticas – Psicoterapia– Psicometría – Argentina; Préférences psychothérapeutiques; Psychothérapie; Psychométrie; Argentine; Preferências psicoterapêuticas; Psicoterapia; Psicometria; Argentina; https://purl.org/pe-repo/ocde/ford#5.01.00